2022
DOI: 10.1007/s10461-022-03607-7
|View full text |Cite
|
Sign up to set email alerts
|

Age and Racial Disparities in Telehealth Use Among People with HIV During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic resulted in widespread telehealth expansion. To determine telehealth uptake and potential sociodemographic differences in utilization among people with HIV (PwH), we examined HIV care appointments at the University of Chicago Medicine, an urban tertiary hospital. Visits between March 15th and September 9th for 2019 and 2020 were categorized as in-person, telehealth, and within telehealth, video, and phone. Differences in visit types were modeled using logistic regression to examine associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
6
15
2
Order By: Relevance
“…Consistent with some previous studies (Friedman et al, 2022;Jewett et al, 2022;Neeman et al, 2021;Pierce & Stevermer, 2020;Rivera et al, 2021;Sachs et al, 2021;Weber et al, 2020;Wegermann et al, 2022), we found that White patients were more likely to use telehealth than Black patients. Unfortunately, limitations of the present data do not allow us to speak to why this is the case-whether this finding reflects shared decision making between clinicians and parents, parent preferences, or clinician preferences alone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with some previous studies (Friedman et al, 2022;Jewett et al, 2022;Neeman et al, 2021;Pierce & Stevermer, 2020;Rivera et al, 2021;Sachs et al, 2021;Weber et al, 2020;Wegermann et al, 2022), we found that White patients were more likely to use telehealth than Black patients. Unfortunately, limitations of the present data do not allow us to speak to why this is the case-whether this finding reflects shared decision making between clinicians and parents, parent preferences, or clinician preferences alone.…”
Section: Discussionsupporting
confidence: 92%
“…The literature on the impact of culture on telehealth usage is inconclusive, and is limited to adult patients; however, the majority of studies suggest that White patients use telehealth services at higher rates than non-White patients. Of the 12 studies that examined telehealth use by race and ethnicity, eight found that White patients used telehealth more than non-White or Hispanic patients during the COVID-19 pandemic (Friedman et al, 2022; Jewett et al, 2022; Neeman et al, 2021; Pierce & Stevermer, 2020; Rivera et al, 2021; Sachs et al, 2021; Weber et al, 2020; Wegermann et al, 2022). All eight of these studies utilized data from medical records to examine telehealth use, and sample sizes ranged from 594 patients to 334,666 visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15][16] For instance, vulnerable populations such as ethnic minorities, low-income individuals and rural residents were less probable to use telehealth services, even after expanding coverage. [17][18][19][20][21][22][23] These disparities could be attributed to limited technological access in vulnerable populations. 18,[24][25][26] Louisiana has a high incidence of T2D and a significant proportion of low-income individuals enrolled in Medicaid.…”
Section: Introductionmentioning
confidence: 99%
“…With the onset of the COVID-19 pandemic in early 2020, HIV care delivery across the United States drastically changed. In-person HIV care appointments were cancelled, and HIV clinics rapidly scaled up telehealth appointments in an attempt to provide continuity of HIV care while protecting PWH from exposure to COVID-19 [6][7][8][9]. It is unclear how these changes in HIV care delivery during the COVID-19 pandemic have impacted traditional measures of retention in care, although some have already proposed including telehealth in retention measures [10,11].…”
Section: Introductionmentioning
confidence: 99%